Peculiarities of Chemical Interaction and Phase Setting in Water-Salt Systems of Nitrates of Cesium, Strontium and Neodymium - Storozhenko, Dmytro; Dryuchko, Oleksandr; Bunyakìna, Natalia; Ivanitcka, Iryna (International Journal of Engineering and Technology, 2018)
The complex study provides a reliable idea of the trends in the joint behavior of structural components in water and salt systems of nitrate precursors of neodymium, cesium, strontium in the preparatory stages of technological regulations for the concentration and immobilization of liquid radioactive waste of the nuclear power industry complex using schemes of porous and layered matrix fixators of 137Cs, 90Sr  radionuclides and thermal activation. Stages of such transformations are revealed; The regularities of complex and phase formation in systems and factors influencing them are determined; A number of physicochemical properties of the intermediate phases formed - the coordination neodymium nitrates: their composition, types of compounds, atomic-crystalline structure, forms of coordination polynuclears Ln, types of coordination of ligands, features and regularities of behavior in the processes of heat treatment were studied. It is established that in the conditions of existence of solutions, the system CsNO3 – Nd(NO3)3 – H2O is characterized by the formation of 2 anionic complex compounds Ln3+, Sr(no3)2 – nd(no3)3 – h2o - eutonic type. Leaking competing reactions are a powerful technological factor that significantly affects the activity of the structural forms of Ln3+. The systematized information allows us to find out the mechanisms, the kinetics of transformations of structural components in similar objects, and enable us to transfer the acquired knowledge system to the plane of promising technological solutions for the solidification of liquid radioactive waste.